Analisis Nilai Karakter Religius dalam Tri Satya Pramuka Bagi Siswa Kelas V SDN 03 Seberang Musi - Anggita, Nice Popia; Tarmizi, Pebrian (Universitas Bengkulu, 2026)
This study aims to determine the relationship of character values ​​in tri satya with religious character values ​​for fifth grade students of SD Negeri 03 Seberang Musi. This research is a qualitative research. The research method used is discourse analysis. The research instrument used is the researcher himself. The data collection technique used is literature study, a type of data collection that uses various literatures such as books, documents, photos and journals. The data analysis technique is qualitative content analysis. The data from the research that was processed obtained six meanings of Tri Satya, of which only four had a correlation between character values ​​and religious character values ​​in Class V SD Negeri 03 Seberang Musi. Based on the results of research in Class V SD Negeri 03 Seberang Musi (1) Class V students at SD Negeri 03 Seberang Musi already have good character values ​​and good religious values ​​(2) Class V students at SD Negeri 03 Seberang Musi already have a tolerant and caring attitude very kind and helpful environment. The conclusion of this study is that the fifth grade students of SD Negeri 03 Seberang Musi have complied with the Tri Satya points relating to the value of religious character.